2010
DOI: 10.1111/j.1365-2435.2009.01649.x
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids may not be responsible for endophyte‐associated reductions in tall fescue decomposition rates

Abstract: Summary1. Fungal endophyte -grass symbioses can have dramatic ecological effects, altering individual plant physiology, plant and animal community structure and function, and ecosystem processes such as litter decomposition and nutrient cycling. 2. Within the tall fescue (Schedonorus arundinaceus) -fungal endophyte (Neotyphodium coenophialum) symbiosis, fungal produced alkaloids are often invoked as the putative mechanism driving these ecological responses. Yet few measurements of alkaloids exist in the ecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
69
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 52 publications
3
69
1
Order By: Relevance
“…This shows that litter N%, even when originating from the limited spatial variation of a homogeneous agricultural soil, can be a main control of litter decomposition and N cycling in grasslands. Since litter N% was not affected by grass endophyte infection in our study, litter N% could not mask any potential alkaloid effects, but such mask is possible in other studies as the endophyte infection has been shown to increase grass green leaf N% (Siegrist et al 2010;Vázquez-de-Aldana et al 2013). In fact, Siegrist et al (2010) speculated that the weak effect of high alkaloid concentrations on decomposition in their study with green leaf material was due to the high N% of the material, which potentially alleviated the adverse alkaloid effects.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…This shows that litter N%, even when originating from the limited spatial variation of a homogeneous agricultural soil, can be a main control of litter decomposition and N cycling in grasslands. Since litter N% was not affected by grass endophyte infection in our study, litter N% could not mask any potential alkaloid effects, but such mask is possible in other studies as the endophyte infection has been shown to increase grass green leaf N% (Siegrist et al 2010;Vázquez-de-Aldana et al 2013). In fact, Siegrist et al (2010) speculated that the weak effect of high alkaloid concentrations on decomposition in their study with green leaf material was due to the high N% of the material, which potentially alleviated the adverse alkaloid effects.…”
Section: Discussionmentioning
confidence: 78%
“…There is also evidence of lower microbial activity and accumulation of organic matter under endophyte infected grass (Franzluebbers et al 1999). These effects are assumed to be due to the alkaloids having adverse effects on soil decomposers (Franzluebbers et al 1999), but this assumption has also been questioned in a study, where high alkaloid concentrations of green grass leaves had only a small negative effect on leaf decomposition in comparison to green leaves with no alkaloids (Siegrist et al 2010). Further investigations of the effects of Epichloë infection on grass litter decomposition are therefore needed (Omacini et al 2012), and so far no study has tested whether the Epichloë effects on litter mass loss translate to changes in nutrient cycling in plant communities with Epichloë infected grasses.…”
mentioning
confidence: 93%
See 3 more Smart Citations